Communication Strategies in Raising Awareness Public Awareness of Toddler Immunization - Rahmad Saputra; Ade Irma; Rusnawati (Winaya Inspirasi Nusantara Foundation, 2019)
Communication strategy is planning (planning) and management (management) to achieve a goal. However, to achieve these goals, it does not function as a road map that only shows the direction, but must be able to show how the operational tactics. The purpose of this study was to determine the communication strategy, the level of public awareness and immunization of toddlers. This research uses descriptive qualitative methods, sampling techniques using purposive techniques. Data collection is done by conducting interviews. The sampling technique uses non-random sampling consisting of people who have toddlers, public health center, Immunization Coordinator, Village Midwife, and Cadres. Based on the results of the study found that the immunization communication strategy is carried out by conducting counseling to the community using media such as brochures, posters, effective communication using language that is easy to understand. To increase immunization coverage, it is necessary to search for toddlers who have not been immunized at home. Increased public awareness in immunization is seen from the number of immunization coverage reports, immunization book guidelines and monthly report results and there are still some people who have not immunized their toddlers because there is no permission from their husbands, where husbands forbid immunization of their children, for fear that their children will have a fever and the issue of fake vaccines that make parents do not want to immunize their toddlers.